ANALISIS PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP HARGA SAHAM (Studi Pada Saham Perusahaan LQ 45 Periode Agustus 2009 – Januari 2012 dan Periode Agustus 2012 – Januari 2015) - Aditya Krisnamurti; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2016)
The aims of this research are to determine: (1) The effect of CSR disclosure on stock prices of companies (2) The effect of companies types in enviromentally sensitive industries to the relationship between disclosure of CSR and stock prices. (3) The difference effect of CSR disclosure on stock prices in before and after the enactment of Government Regulation No. 47 of 2012 regarding Corporate Social Responsibility Limited Liability Company. The population of this report is a company that consistently in LQ 45 on period August 2009 – January 2012 and August 2012 – January 2015. This report uses purposive sampling methods in collecting data. There are 17 companies that are consistent in the distribution of the two periods, or the total amount about 102 companies in six years of observation. The method of analysis in this research is multiple regression analysis, moderated regression analysis, and Chow test.The result of this research shows that the disclosure of CSR does not affect the company’s stock price LQ 45. The types of companies that are sensitive to the environment as a moderating variable can not affect the relationship of CSR disclosure and stock prices. The stock price of companies at LQ 45 is higher after the enactment of Government Regulation No. 47 of 2012 regarding Corporate Social Responsibility Limited Liability Company.